ALOKASI PENGELUARAN RUMAH TANGGA UNTUK KONSUMSI BAHAN PANGAN DI KELURAHAN KEBUMEN KABUPATEN KEBUMEN - Ken Suratiyah; Nita Astriana; Lestari Rahayu Waluyati (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2010)
The objectives of this paper are (1) to know how much household expenditure allocation for food consumption in Kelurahan Kebumen, (2) to know the factors affecting household expenditure allocation for food consumption in Kelurahan Kebumen. Household expenditure allocation for food consumption in kelurahan Kebumen is food expenditure percentage to total income for a month. Affecting factors were analyzed by multiple regression analysis. Dependent variable used is householod expenditure allocation for food consumption and independent variables used are the number of family members, wife’s age, education level of husband, education level ofwife, husband’s work time, wife’s work time, comparison of adult member with totally family members, and household’s income. The result show that household expenditure allocation for food consumption in Kelurahan Kebumen IS 51,33% of total income, it means that household in Kelurahan Kebumen are still poor. Affrcting factors to household expenditure allocation for food consumption in Kelurahan Kebumen are the number of family members, comparison of adult with totally familt members, and household income.